Goldilocks Effect of Base Strength on Site Selectivity in Acylation of Amphiphilic Diols - Fallek, Reut; Ashush, Natali; Fallek, Amit; Portnoy, Moshe (Synlett, 2021)
Two series of competitive acylation experiments with a polar and an apolar alcohol substrate, imitating two parts of amphiphilic diols, examined the influence of bases of varying strength on the substrate selectivity. While weakly basic 2,4,6-collidine only mildly accelerates the acylation of the polar substrate without affecting that of the apolar one, the acylation of both substrates is drastically hastened by strongly basic DBU. In both cases there is a notable, though not overwhelming, shift of the substrate selectivity towards the polar substrate, compared to the base-free acylation, which favors that of the apolar one. The extraordinarily strong change in the substrate selectivity in favor of the polar substrate was induced, however, by aliphatic tertiary amine bases, DIPEA and Et3N, of ‘Goldilocks’ moderate base strength, which strongly accelerate the acylation of the polar substrate, while almost not affecting that of the apolar one. These effects of the bases on the substrate selectivity are reflected in the site-selectivity trends observed in the acylation of a model diol amphiphile.
Keywords: acylation; site selectivity; substrate selectivity; basicity; amphiphiles